PENGARUH PENGUASAAN KOSAKATA DAN RASA PERCAYA DIRI TERHADAP PRESTASI BELAJAR BAHASA INGGRIS - Siti Habibah (Universitas Indraprasta PGRI, 2019)
Abstract: This aims to analyze the effect simultaneously and partially of vocabulary mastery and self-confidence on English learning achievement, especially vocation middle school students in English subjects. The research method used surveys with correlation and regression analysis, that is connected between data showing vocabulary mastery and self-confidence with data showing English learning achievement, it can be concluded that: (1) there is a significant influence of vocabulary and self-confidence together to the English learning achievement’sstudents, this is proved by Sig = 0.000 <0,05 and Fcount = 43.918; (2) there is a significant influence of vocabulary mastery on the English learning achievement’sstudents, this is proved by the value of Sig = 0.000<0.05 and tcount = 5.406; and (3) there is a significant influence of self-confident on the English learning achievement’s students, this is proved by the value of Sig = 0.000 < 0.05 and tcount = 4.338.Keywords: vocabulary mastery; confidence; EFL students